2018
DOI: 10.1021/acsami.7b18896
|View full text |Cite
|
Sign up to set email alerts
|

“Triple-Punch” Anticancer Strategy Mediated by Near-Infrared Photosensitizer/CpG Oligonucleotides Dual-Dressed and Mitochondria-Targeted Nanographene

Abstract: Nanomedicine-based combination therapy has sparked a growing interest in clinical disease treatment and pharmaceutical industry. In this study, a mitochondria-targeted and near-infrared (NIR) light-activable multitasking nanographene (i.e., GT/IR820/DP-CpG) was engineered to in situ trigger highly efficient "triple-punch" strategy of cancer photodynamic therapy, photothermal therapy, and immunotherapy. Modification of triphenylphosphonium on graphene made the vehicle specifically guide the NIR dye IR820 home t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 68 publications
(134 reference statements)
0
34
0
Order By: Relevance
“…The high lipophilicity of TPP with three aromatic rings and a positive charge on phosphorous enhanced the cell association and access to mitochondria. Further, the introduction of the immunostimulatory conjugate (i.e., cytosine−guanosine oligodeoxynucleotides) increased the production of proinflammatory cytokines (i.e., interleukin-6, tumor necrosis factor-α, and interferon-γ), thus, modulating the tumor immunogenicity [ 50 ]. From experimental data emerged that target nanophototherapeutics, generating ROS and heat, ultimately kill cancer cells by inducing mitochondrial collapse and irreversible cell apoptosis upon NIR laser irradiation and the target systems prompted much higher early apoptosis than non-target counterparts.…”
Section: Subcellular Localization Of Functional Graphene Nanomatermentioning
confidence: 99%
“…The high lipophilicity of TPP with three aromatic rings and a positive charge on phosphorous enhanced the cell association and access to mitochondria. Further, the introduction of the immunostimulatory conjugate (i.e., cytosine−guanosine oligodeoxynucleotides) increased the production of proinflammatory cytokines (i.e., interleukin-6, tumor necrosis factor-α, and interferon-γ), thus, modulating the tumor immunogenicity [ 50 ]. From experimental data emerged that target nanophototherapeutics, generating ROS and heat, ultimately kill cancer cells by inducing mitochondrial collapse and irreversible cell apoptosis upon NIR laser irradiation and the target systems prompted much higher early apoptosis than non-target counterparts.…”
Section: Subcellular Localization Of Functional Graphene Nanomatermentioning
confidence: 99%
“…However, RNA and DNA oligonucleotides, including MBs, are rapidly degraded under physiological conditions, and the negatively charged oligonucleotides are difficult to internalize into cancer cells; therefore, they have limited utility as therapeutic agents 11. Fortunately, the advent of nanotechnology has led to the development of different kinds of gene delivery systems, such as mesoporous silica nanoparticles 12, nanographene 13, PLGA-based nanoparticles 14, gold nanoparticles 15, and iron oxide nanoparticles. Such delivery systems are able to protect and transfer plasmid DNA 16, 17, oligonucleotides 18 and fluorescent probes 19 into living cells.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo results demonstrated that GT/IR820/DP-CpG shows significant inhibition of tumor growth (tumor inhibition rate approximately 88%) which resulted from the combination of the photothermal effect of IR 820 and immunostimulatory activity of DP-CpG ( Fig. 5 ) [105] .
Fig.
…”
Section: Nanocarriers For Mitochondrial Targeting In Diagnosis and Treatment Of Cancermentioning
confidence: 98%